1990
DOI: 10.1002/mrm.1910150116
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional spectra of intact tissue: Homonuclear Hartmann‐Hahn spectroscopy provides increased sensitivity and information content as compared to COSY

Abstract: Hartmann-Hahn (HOHAHA) spectroscopy led to good definition of proton spin systems of metabolites such as lactate, (phospho) creatine, and carnosine from a 3-g sample of excised frog gastrocnemius muscle in a 17-min experiment. The sign of the HOHAHA cross-peak intensity appears to provide additional information about interactions between metabolites and their protein binding sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…3). Alonso et al [13] observed a connectivity between these two subgroups in 2D HOHAHA experiments on intact frog m. gastrocnemius, which proves additionally that both subgroups are restricted in mobility. The experiments on human calf muscle demonstrate that the interaction of the protons within each group is the dominant one owing to the strong spatial dependence of the direct spin-spin coupling.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…3). Alonso et al [13] observed a connectivity between these two subgroups in 2D HOHAHA experiments on intact frog m. gastrocnemius, which proves additionally that both subgroups are restricted in mobility. The experiments on human calf muscle demonstrate that the interaction of the protons within each group is the dominant one owing to the strong spatial dependence of the direct spin-spin coupling.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding the cause of the observed residual dipolar couplings of intramyocellular metabolites, the intrinsic muscle structure must play a crucial role as demonstrated in HOHAHA experiments [13] where negative ROE cross peaks indicating temporal binding of Cs and (P)Cr could only be observed in intact tissue samples and not in muscle tissue extracts and model solutions. Constraints of the molecules between the highly ordered actin-myosin chains or attachment to macromolecules (which could themselves be ordered within the cells) were discussed first [6].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been several studies in frogs (gastrocnemius biopsies observed with DQF-COSY [57] or with HOHA-HA (HOmonuclear HArtmann HAhn spectroscopy) [47]) sequences and rats (orientation-dependant dipolar coupling in lactate resonance in biopsy muscle studied by DQF and J-resolved 1 H NMR [132]). However, most of these in vitro 2D MRS studies have been performed in mice.…”
Section: Applications To Musclementioning
confidence: 99%
“…Total correlation spectroscopy (TOCSY) [45,46] has been used to study muscle lipids [47,48]. This sequence provides all the correlations in a coupling network, resulting in a more characteristic fingerprint of the molecule.…”
Section: D Correlation Spectroscopymentioning
confidence: 99%